Observational and Genetic Evidence Reveals the Effect of Serum Lipid Levels on COPD Risk - Jia G; Guo T; Liu L; He C (International Journal of COPD)
Guobing Jia,1,2 Tao Guo,1 Lei Liu,3 Chengshi He2 1School of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of China; 3Department of Respiratory and Critical Care Medicine, Chongqing Hospital of Traditional Chinese Medicine, Chongqing, People’s Republic of ChinaCorrespondence: Chengshi He, Email 18408293045@163.comBackground: Disorders of lipid metabolism are linked to an increased risk of various diseases; however, their association with chronic obstructive pulmonary disease (COPD) remains unclear. This study aimed to examine the relationship between serum lipid levels and COPD risk.Methods: The methods of the National Health and Nutrition Examination Survey (NHANES) and Mendelian randomization (MR) analyses were employed to investigate the relationships between lipids and COPD across multiple populations. Data from 2013 to 2023 were selected for the NHANES study on US population, and weighted multivariable-adjusted logistic regression was employed as the primary statistical method. And data utilized for the MR analysis were derived from genome-wide association studies (GWAS) conducted on European and East Asian populations, with inverse-variance weighted (IVW) method serving as the principal statistical approach.Results: The NHANES analyses indicated that higher levels of total cholesterol (TC) (OR = 0.85, 95% CI = 0.77– 0.93), non-high-density lipoprotein cholesterol (non-HDL-C) (OR = 0.86, 95% CI = 0.78– 0.94) and low-density lipoprotein cholesterol (LDL-C) (OR = 0.85, 95% CI = 0.74– 0.97) were associated with a reduced risk of COPD in the US population. In the MR analyses, TC (OR = 0.90, 95% CI = 0.84– 0.95), non-HDL-C (OR = 0.91, 95% CI = 0.85– 0.96), and LDL-C (OR = 0.88, 95% CI = 0.82– 0.94) were causally linked to a decreased risk of COPD in the European population. Similar associations were observed in the East Asian population.Conclusion: Our study identified associations between TC, non-HDL-C, and LDL-C with a reduced risk of COPD. This underscores the importance of monitoring lipid metabolism in patients with COPD and provides supporting evidence for the use of lipid-based therapies in its treatment.Keywords: lipids, COPD, association, NHANES, Mendelian randomization